2011
DOI: 10.18388/abp.2011_2266
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds from Achillea millefolium L. and their bioactivity.

Abstract: Since antiquity, Achillea millefolium L. (Asteraceae) has been used in traditional medicine of several cultures, from Europe to Asia. Its richness in bioactive compounds contributes to a wide range of medicinal properties. In this study, we assessed A. millefolium methanolic extract and its isolated components for free radical scavenging activity against 2,2-diphenyl-pycrilhydrazyl, total antioxidant capacity (based on the reduction of Cu(++) to Cu(+)), and ability to inhibit lipid peroxidation. The activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 28 publications
9
78
0
5
Order By: Relevance
“…The phytochemical profile of A. millefolium showed also relevant contents in organic acids (mainly oxalic, quinic, and citric), FA (with linoleic and palmitic acids as the major ones) and tocopherols (specially, ␥-tocopherol) (Benedek et al, 2007;Dias et al, 2013;Gharibi et al, 2013;Vitalini et al, 2011).…”
Section: Antioxidant Potential Of Asteraceae Species With Botanical Rmentioning
confidence: 99%
“…The phytochemical profile of A. millefolium showed also relevant contents in organic acids (mainly oxalic, quinic, and citric), FA (with linoleic and palmitic acids as the major ones) and tocopherols (specially, ␥-tocopherol) (Benedek et al, 2007;Dias et al, 2013;Gharibi et al, 2013;Vitalini et al, 2011).…”
Section: Antioxidant Potential Of Asteraceae Species With Botanical Rmentioning
confidence: 99%
“…Achillea millefolium L., known as yarrow, is a member of the Asteraceae family and has been used in folk medicine for hundreds of years in many countries ranging from Europe to Asia [5]. Yarrow has been traditionally used to treat inflammatory and spasmodic gastrointestinal disorders, hepatobiliary complaints and overactive cardiovascular and respiratory ailments [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research on the phytochemical composition of A. millefolium has shown that it contains an abundance of phenolic compounds, such as flavonoids and phenolic acids [5,7]. Furthermore, some—but not enough—studies have revealed the chemical components of its essential oil [1921].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse medicinal properties have been reported for its extract such as gastroprotective and antiulcerogenic, and anti-inflammatory Potrich et al 2010). Besides, its essential oil and compounds also showed antioxidant activity (Candan et al 2003;Raudonis et al 2009;Vitalini et al 2011 scavenging properties of A. millefolium, we have evaluated the effects of the 7-day exposure to AE on antioxidant system of rats. Besides, we also investigated the effect of this extract on hepatic enzymes after acetaminophen-induced hepatotoxicity in mice.…”
Section: Modulation Of Antioxidant Systems By Subchronic Exposure To mentioning
confidence: 99%